Perubahan Sifat Kimia Inceptisol Melalui Aplikasi Bahan Humat Ekstrak Gambut Dengan Inkubasi Dua Minggu - Jeni Swanda; Hamidah Hanum; Purba Marpaung (Jurnal Agroekoteknologi, 2015)
The objective of this research was study of several dosages humic material from extract peat inimproving Inceptisol soil chemical characteristics .The soil sample using Inceptisol and humicmaterial from extract peat. It is conducted in Faculty of Agriculture greenhouses, University ofNorth Sumatra, using non-factorial randomized block design,the treatment of humic materialconsisted of 6 levels and 3 replications so there are 18 experimental units, namely : The treatment 0,200, 400, 600, 800 and 1000 ppm humic material. The measured parameters were pH (H2O), Corganic,P-available,Al-exchange, cation exchange capacity (CEC) and Al saturation. The result ofthis research showed that humic material application significantly affected in increasing pH and Corganik,but not significant effect on P-available,Al-exchange, CEC and Al saturation. The value ofsoil pH increasing from very acid to acid on dosages humic material 400 until 1000 ppm and thehighest increase of soil pH is 4.74 on dosages 1000 ppm. Humic material couldn’t improve otherssoil chemical characteristics. The value of P-available, C-organic, Al saturation is very low, andCEC is low.Key words: Inceptisols, humic material, pH, C-organik, P-avalaible,CEC and Al-exchange